Edition of the Armenian Monothelitism of the History of Agathangelos - Sahakyan, Artsruni (Bulletin of Yerevan University B: Philology, 2023)
In the 30s of the 7th century, the new confessional political course announced by Emperor Herakles, the Doctrine of Monothelitism, reached Armenia during the reign of Catholicoses Yezr and Nerses. But the Armenian Monothelitism was not created parallel to the Armenian traditional church, like the Armenian Chalcedonian church decades ago during the reign of Emperor Morik, but instead of it, only changing the nature of the latter. Catholicos Nerses Tayetsi established a new residence for the new church in Zvartnots and built a new cathedral named Saint Zvartnots, with such opulent and magnificent architecture that it overshadowed not only the cathedrals of Etchmiadzin and Dvin, but also the Chalcedonian cathedral of Avan. The consecration ceremony of Zvartnots Cathedral was attended by Byzantine Emperor Constantine, the financial sponsor of the temple, who liked the new temple so much that he wished to have a similar temple in the neighborhood of Saint Sofia, in the capital. That is why he took with him Hovhan, the old-aged architect of Zvartnots, who unfortunately died on the way. The Armenian Monothelitism, which survived until the end of the century, created a new edition of Agathangelos in accordance with its new creed, which, at the same time, was translated into Greek and reached us in a form of a manuscript preserved in the Ohrid library, which was discovered by the famous orientalist Gerard Garret.